Historical Analysis and Impact of Islamic Socio-Political Developments During the Abbasid Period - Refani Nafi Sara; Nadhirotul Jannah; Noer Cahya Khoirony; Mashudi (Penerbit Hellow Pustaka, 2025)
The chronicles of the Islamic dominion commenced following the passing of Prophet Muhammad SAW in the year 632 AD. and the presence of Khalfur Rasidin, the Umayyad and Abbasid dynasties. On the other hand, the Mamluk dynasty in Egypt and the great kingdoms of Turkey, Iran, and India remained strong. Third, modern Islamic movements such as the Wahhabi movement are pure reformist movements (Salafiyyah). This inquiry endeavors to delve into the intricate social fabric of Islamic communities and the dynamics of social mobility within them. The approach employed in this study is qualitative, utilizing the method of literature review. Research shows that during the Abbasid period, support for Arabs as a ruling class declined, providing opportunities for all groups to advance in social status.